Pengembangan Sistem Informasi Manajemen Arsip Surat Berbasis User Form Excel VBA dalam Meningkatkan Mutu Layanan Administrasi di SDS Miftahul Falah Silo - Rif'ah Mellati Fifitrotin; Totok Sudarmanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
In educational institutions, incoming and outgoing letters have important administrative and legal values ​​in educational operations. Therefore, the management of letter archives plays a strategic role in maintaining the smooth running of administrative activities and as a source of academic information for educational institutions. The formulation of the research problem is: (1) How is the validity of the Letter Archive SIM Based on Excel VBA User Form in improving the quality of administrative services at SDS Miftahul Falah Silo? (2) How is the practicality of the Letter Archive SIM Based on Excel VBA User Form in improving the quality of administrative services at SDS Miftahul Falah Silo? (3) How is the effectiveness of the Letter Archive SIM Based on Excel VBA User Form in improving the quality of administrative services at SDS Miftahul Falah Silo? This research was conducted at SDS Miftahul Falah Silo using the Research and Development (R&D) method of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Product trials used internal and external trials involving validators and users. The data collected consisted of quantitative and qualitative data obtained through observation, interviews, documentation, and questionnaires. The results of the study indicate that (1) the system is highly feasible to use, as evidenced by the validity test results with an average value of 93.5%. (2) the practicality test results indicate the system is very practical with an average value of 91.6%. (3) based on the Wilcoxon signed rank test with a Z-value of -3.923 and a significance level of <0.001, and the N-Gain test results of 0.7254 indicate that the system is highly effective in improving the quality of administrative services.